Spatial and Temporal Distribution of Forest Fires in Mahdesh Province - Chaudhary, Sanjay Kumar; Manjan, Shiv Kumar; Yadav, Shailendra Kumar; Parajuli, Ashok; Manjan, Jyoti (International Research Journal of MMC, 2026)
Forest fires are the main causes of forest degradation worldwide, and Madhesh Province in Nepal is highly vulnerable despite its limited forest cover. This study analyzes the spatial and temporal distribution of forest fires in Madhesh Province and identifies fire risk zones using Remote Sensing (RS) and Geographic Information System (GIS) techniques. Key influencing factors are land cover, slope, aspect, elevation, land surface temperature, proximity to settlements, and to roads were integrated using a Fire Risk Index method. The final risk map classified the area into five categories are very low, low, moderate, high, and very high. Validation was conducted using VIIRS S-NPP fire incidence data from March 2012 to April 2022. A total of 28,619 fire incidents and fire density 0.14 were recorded, with the highest number in 2021 (4,173). Approximately 93% of fires occurred during the hot and dry season (March to mid-June), with March alone accounting for 52%. Parsa District experienced the highest number of incidents. Notably, 67.5% of fires occurred within high and very high-risk zones, which covers 51.75% of the study area, confirming the model’s reliability. The development of a forest fire risk zone map provides crucial data for understanding the forest fire problem and may serve as an effective tool for the Ministry of Forests and Environment, provincial and local governments, and other relevant authorities. The planning, prevention, and mitigation of forest fires will be made easier with the use of this data, improving risk management.